A Model of Employee Happiness among Researchers in Beijing M Medical Research Center - Jian, Li; Ruanggoon, Jirapong; Wisedsind, Noppawan (Science, Technology, and Social Sciences Procedia, 2024)
The research objectives were as follows: 1) To investigate the influence of achievement, work itself, personal growth, promotion, and recognition on job satisfaction; 2) To investigate the influence of achievement, work itself, personal growth, promotion, and recognition influence on employee happiness; 3) To investigate the influence of job satisfaction on employee happiness; and 4) To propose a model of employee happiness among researchers in BEIJING M Medical Research Center. This research used quantitative approach. The data collected through questionnaire surveys from the sample, which comprised 240 researchers at the BEIJING M Medical Research Center who were involved in research activities and played core roles and functions within the research center’s business operations, was obtained through a randomized process. The data was analyzed using statistics such as frequency, percent, mean, and standard deviation, as well as measures of skewness, kurtosis, correlation, and multiple regression.The research findings revealed that: 1) Work itself, personal growth, promotion, and recognition had a positive influence on employee happiness; 2) The personal growth, promotion, and recognition had a positive influence on the job satisfaction; 3) Employee job satisfaction had a positive influence on employee happiness at the Bejing M Medical Research Center.; and 4) The model of employee happiness among researchers at the BEIJING M Medical Research Center was shaped by several key factors. Firstly, the manageable and enjoyable nature of their work, coupled with a high level of understanding, fostered positivity towards their responsibilities. Personal growth was nurtured through career development initiatives and tailored learning opportunities, reinforcing the connection between growth and the organization’s learning environment. Fair promotion processes and recognition validated skills and efforts, contributing to a sense of appreciation within the community. These elements collectively led to researchers’ job satisfaction, characterized by contentment, commitment, contribution, and a positive outlook on development.